Behind a Digital Mask: Users' Subjective Experience of Animated Characters and Its Effect on Source Credibility. Issue 5 (10th February 2022) - Di Natale, Anna Flavia; Triberti, Stefano; Sibilla, Federica; Imperato, Chiara; Villani, Daniela; Mancini, Tiziana; Riva, Giuseppe
Abstract: Recently, computer-mediated communication has incorporated animated characters (ACs) as interface technologies. These digital entities are animated by mimicry and can be used either to deliver pre-recorded messages or to live communicate with others. The interlocutors can choose the physical appearance of the character and decide to use a character that may or may not represent their actual self. In this respect, it is important to investigate the psychological mechanisms describing how the user responds to ACs and the resulting effects on communication. To do this, a 2 × 2 experiment was conducted ( n  = 85) to evaluate the effects of human-likeness (human-like vs. non-human-like) and self-representation (actual self vs. ideal self) on users' subjective experience, in terms of para-social relationship, identification and emotions, and its effect on communication-related variables such as source credibility. Results showed that, unlike self-representation, human-likeness had a significant effect on the interaction between the user and an AC, with non-human-like ACs stimulating a more engaging and positive interaction compared with human-like ACs. Data also confirmed the importance of para-social relationship and identification in fostering source credibility. Theoretical and practical implications are discussed.